Energy Governance, Economic Development, and Human Rights Protection in Resource-Rich Regions: Evidence from Indonesia - Teguh Permana; Andriani Puspitaningsih (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Energy governance has become an increasingly important issue in resource-rich regions where economic development driven by energy extraction often intersects with concerns about human rights protection. In many developing countries, including Indonesia, the expansion of energy projects has generated significant economic benefits while simultaneously raising questions regarding the protection of local communities’ rights, the equitable distribution of economic benefits, and the effectiveness of legal institutions in regulating energy resources. This article examines how energy governance frameworks influence economic development and human rights protection in resource-rich regions. The study adopts a socio-legal perspective that positions energy governance within broader institutional and regulatory structures shaping the relationship between economic growth and community rights. Using a qualitative approach, the research employs descriptive analysis and content analysis of relevant legal frameworks, policy documents, and governance practices related to energy resource management. Through this analysis, the article explores how governance arrangements mediate the interaction between economic development objectives and human rights obligations. The findings indicate that although energy development contributes to regional economic growth, governance challenges, including weak regulatory enforcement and limited community participation, often hinder the effective protection of economic and social rights. Strengthening governance accountability, enhancing institutional coordination, and integrating human rights principles into energy policy are therefore crucial for ensuring more equitable and sustainable development in resource-rich regions. [Tata kelola energi telah menjadi isu yang semakin penting di wilayah kaya sumber daya, di mana pembangunan ekonomi yang didorong oleh ekstraksi energi sering kali beririsan dengan perlindungan hak asasi manusia. Di banyak negara berkembang, termasuk Indonesia, ekspansi proyek energi menghasilkan manfaat ekonomi yang signifikan sekaligus menimbulkan pertanyaan terkait perlindungan hak masyarakat lokal, distribusi manfaat ekonomi yang adil, serta efektivitas institusi hukum dalam mengatur sumber daya energi. Artikel ini mengkaji bagaimana kerangka tata kelola energi memengaruhi pembangunan ekonomi dan perlindungan hak asasi manusia di wilayah kaya sumber daya. Penelitian ini menggunakan perspektif sosio-legal yang menempatkan tata kelola energi dalam struktur kelembagaan dan regulasi yang lebih luas, yang membentuk hubungan antara pertumbuhan ekonomi dan hak-hak masyarakat. Menggunakan pendekatan kualitatif, penelitian ini menerapkan analisis deskriptif dan analisis isi terhadap kerangka hukum yang relevan, dokumen kebijakan, serta praktik tata kelola terkait pengelolaan sumber daya energi. Melalui analisis tersebut, artikel ini mengeksplorasi bagaimana pengaturan tata kelola memediasi interaksi antara tujuan pembangunan ekonomi dan kewajiban perlindungan hak asasi manusia. Temuan penelitian menunjukkan bahwa meskipun pembangunan energi berkontribusi terhadap pertumbuhan ekonomi daerah, tantangan tata kelola—termasuk lemahnya penegakan regulasi dan terbatasnya partisipasi masyarakat—sering kali menghambat perlindungan efektif terhadap hak-hak ekonomi dan sosial. Oleh karena itu, penguatan akuntabilitas tata kelola, peningkatan koordinasi kelembagaan, serta integrasi prinsip-prinsip hak asasi manusia ke dalam kebijakan energi menjadi langkah penting untuk memastikan pembangunan yang lebih adil dan berkelanjutan di wilayah kaya sumber daya.]